Model Pengambilan Keputusan Dalam Diplomasi Konflik: Kajian Teoretis Literatur Indonesia Dan Implikasinya Pada Krisis Sudan 2025 - Azka Fathan Fansuri; Dewi Lestari (Universitas Islam Indragiri, 2025)
The protracted conflict in Sudan in 2025 illustrates repeated failures in implementing ceasefire agreements, driven largely by unstable domestic political dynamics and overlapping external interventions. This study analyzes the key determinants shaping ceasefire breakdowns by examining the interaction between domestic elite interests, fragmentation among armed groups, and international pressures. The research aims to provide an in-depth understanding of how military and political elites influence the trajectory of conflict and diplomacy. The study employs a qualitative research design based on document analysis, literature review, and policy examination related to the dynamics of SAF, RSF, and regional actors. Data were analyzed using decision-making theory and conflict diplomacy frameworks to identify behavioral patterns and strategic interests affecting negotiation processes. The findings reveal that ceasefire failures stem from incompatible elite power calculations, weak command structures, and external support that sustains conflict dynamics. Moreover, fragmented positions among regional mediators further reduce the effectiveness of multilateral diplomatic efforts. The study concludes that Sudan’s diplomatic failures are structural, shaped by the interactions between domestic elite decision-making and geopolitical contestation that together create disincentives for peaceful resolution. These results highlight the need for mediation approaches that are more realistic, adaptive, and oriented toward creating strategic incentives for involved elites.